The differentiated STEM approach in problem-based learning: Can it enhance students’ critical thinking skills in basic chemistry laws - Majid, Karima; Mulyani, Sri; Ulfa, Maria; Shidiq, Ari Syahidul (Pascasarjana Universitas Negeri Medan, 2024)
The 21st century highlights the critical role of education in developing life skills, including critical thinking, to address rapid global changes. The learning process in schools becomes a critical factor in strengthening these skills. Therefore, this study aims to determine the effect of the Differentiated Problem-Based Learning (PBL) model with the STEM approach on students' critical thinking skills on basic chemical laws in class X of a Senior High School in Surakarta. Samples were selected using cluster random sampling to choose two classes as samples, namely, the experimental and control classes. Research data was collected through a post-test using an essay measuring students' critical thinking skills. The results were analyzed using the Kruskal-Wallis’s test based on the mean post-test scores of the experimental class (73.00) and the control class (64.4), yielding a significance value of 0.004 (< 0.05). These results indicate a positive effect of Differentiated PBL-STEM on students' critical thinking skills. Skilled group students consistently demonstrated critical thinking skills, while students in the intervention and intermediate groups showed improvements from the initial diagnostic results of the learning process.